Feelings and uncertainty present in venezuelan economic news under a fuzzy focus (Gestión y Gerencia, 2025)
This article presents some results and contributions that are based on a broader research work whose central problem is aimed at estimating the feelings and uncertainty present in Venezuelan economic news. Five main objectives were raised. Only one of them is shown in this manuscript: Estimate those feelings and uncertainty through fuzzy logic. Conceptually, the research focuses on the domain of Fuzzy Logic and feelings. Methodologically, the study is immersed in the Empirical Analytical research perspective. A Fuzzy Inference System (SIB) was built from the analyzed data. The empirical results indicate that the average presence of feelings (5) in the news shows a very high presence of uncertainty (6.75), demonstrating with this that the SIB is efficient and that feelings can be measured in correspondence with what was expressed by Jevons (1871/1988), Keynes (1936/1965) and Kahneman & Tversky (1987).
Keywords: Economic news; Fuzziness; Uncertainty; Feelings